3-D simulation of flow behaviour and film distribution outside a horizontal tube. (April 2017) - Qiu, Qinggang; Meng, Chuiju; Quan, Shenglin; Wang, Weishu
Highlights: Flow behaviour of liquid film over horizontal tube was 3-dimensionally simulated. The saddle-shaped spreading liquid lamella was formed with single liquid column. The maximum elongation distance of liquid film was obtained in the axial direction. A crest was formed between the two columns. The maximum film thickness was over three times the minimum in the axial direction. Abstract: The behaviour of falling film has significant effects on the efficiency of heat and mass transfer. Therefore it is important to study on the distribution of the film thickness around a tube in both the circumferential and axial directions. A 3-D model was applied in this study to simulate the falling film flow process of a column flow outside a horizontal tube, of which the Reynolds number varied from approximately 171 to 368. The results showed that with a single liquid column, a saddle-shaped spreading liquid lamella was formed along the axial direction, and the maximum elongation distance of the liquid film was obtained in the axial direction. In contrast, with two adjacent liquid columns, the flow behaviour changed a lot due to the interaction between the columns. A crest was formed between the two columns, and the maximum film thickness was more than three times of the minimum in the axial direction. In addition, the film thickness in the central section of the liquid column was extracted. It rapidly decreased as the circumferential angle varied from 20° to 60°. Then it changed little in the range of 60–120°, and sharply increased in the range of 120–150°.